A Review of the Application of Renewable Resources in Preparing Acrylic Polymer Latex. Issue 1 (February 2016) - Bao, Zhongbin; Li, Wen; Fu, Zhengrong; Chen, Lijun
Acrylic polymer latex plays an important role in many industrial processes, such as the production of synthetic rubber, surface coatings, adhesives, additives in paper and textiles and many other products. Presently, the raw materials for preparing the acrylic polymer latex mainly originate from fossil resources. The progressive decline of fossil resources, together with the ongoing increases in oil prices, has initiated an increase in the search for alternatives, based on renewable resources for the production of acrylic polymer latex. In this paper, the application of renewable resources in preparing acrylic polymer latex is reviewed and summarized. The aim of the review is that provides the reference for application of the renewable resources in preparing the acrylic polymer latex.